2018
DOI: 10.1142/s0217751x18501580
|View full text |Cite
|
Sign up to set email alerts
|

The study of a half-spin relativistic particle in the rotating cosmic string space–time

Abstract: In this paper, a charged half-spin particle depicted by the Dirac equation in the presence of a uniform magnetic field and a mixed potential are analyzed in the rotating cosmic string space–time. In order to facilitate this study, we assume that the symmetrical center of the potential is on the string and the magnetic field is parallel to the string. Based on the functional analysis method, we obtain the energy eigenvalues for different physical situations. It shows that the energy levels of the system depend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…We have shown that the energy levels of the particle and antiparticle depend on the values of the physical parameters involved. In the case of energy (71), its validity is conditioned to Equation (72). Depending on the choice we make for the parameters, we can obtain forbidden energies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have shown that the energy levels of the particle and antiparticle depend on the values of the physical parameters involved. In the case of energy (71), its validity is conditioned to Equation (72). Depending on the choice we make for the parameters, we can obtain forbidden energies.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we will choose an appropriate tetrad basis and implement the field configuration involved through the performing of a minimal substitution. The spacetime induced by a rotating cosmic string is described by the metric [72,77,78].…”
Section: Dirac Equation In the Spinning Cosmic String Spacetimementioning
confidence: 99%
See 2 more Smart Citations
“…The differential equations (60) and (61) can be placed in an convenient mode using, respectively, the following solutions:…”
Section: The Analysis Of Both the Spin And The Pseudo-spin Symmetriesmentioning
confidence: 99%